Recent advances on the δ opioid receptor: from trafficking to function. (1st July 2014) - Gendron, Louis; Mittal, Nitish; Beaudry, Hélène; Walwyn, Wendy
<x xml:space="preserve">Abstract</x> Within the opioid family of receptors, δ (DOPrs) and μ opioid receptors (MOPrs) are typical GPCRs that activate canonical second‐messenger signalling cascades to influence diverse cellular functions in neuronal and non‐neuronal cell types. These receptors activate well‐known pathways to influence ion channel function and pathways such as the map kinase cascade, AC and PI3K. In addition new information regarding opioid receptor‐interacting proteins, downstream signalling pathways and resultant functional effects has recently come to light. In this review, we will examine these novel findings focusing on the DOPr and, in doing so, will contrast and compare DOPrs with MOPrs in terms of differences and similarities in function, signalling pathways, distribution and interactions. We will also discuss and clarify issues that have recently surfaced regarding the expression and function of DOPrs in different cell types and analgesia. Linked Articles This article is part of a themed section on Opioids: New Pathways to Functional Selectivity. To view the other articles in this section visit http://dx.doi.org/10.1111/bph.2015.172.issue-2